Gry językowe w tytułach prasowych = Language games in press titles - Rej, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is an analysis of words plays in selected press titles. The work uses titles of weekly opinion-forming newspapers such as "Wprost", "Newsweek", "Do Rzeczy", "Gazeta Polska", "wSieci". The research material (more than a hundred covers from 2000-2021) was analyzed in a descending hierarchy i.e. from the smallest unit to elaborate word structures.
Keywords: tytuły; gry językowe; multimodalność; intertekstualność; titles; language games; multimodality; intertextuality